2020
DOI: 10.1177/1550147720968469
|View full text |Cite
|
Sign up to set email alerts
|

Traffic travel pattern recognition based on sparse Global Positioning System trajectory data

Abstract: This article mainly uses sparse Global Positioning System trajectory data to identify traffic travel pattern. In this article, the data are preprocessed and the eigenvalues are calculated. Then, the Global Positioning System track points are identified and extracted by walking and non-walking segments. Finally, the three machine learning models of support-vector machine, decision tree, and convolutional neural network are used for comparison experiments. The innovation of this article is to propose a walking a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…In Figure 4, TW 8 is a special window. Time Step 4 is followed by time Step 7 in TW 8 in the test trajectory, which means that time steps (5,6,7) are in the same grid. ere is 30 seconds between time Step 4 and time Step 7.…”
Section: Definition 8 (Construct Empirical Local Temporal Windowmentioning
confidence: 99%
See 1 more Smart Citation
“…In Figure 4, TW 8 is a special window. Time Step 4 is followed by time Step 7 in TW 8 in the test trajectory, which means that time steps (5,6,7) are in the same grid. ere is 30 seconds between time Step 4 and time Step 7.…”
Section: Definition 8 (Construct Empirical Local Temporal Windowmentioning
confidence: 99%
“…In particular, during major events such as the ceremony, concert, and games, real-time monitoring and anomaly detection of the logistics vehicles trajectories have attracted a large amount of security concern since the tragedy in Nice (86 dead and 458 injured) [1] and Barcelona (15 dead and 100 injured). As the vehicle trajectory data can be conveniently collected nowadays by digital sensors, such as various navigation systems, smart cellphones, and RFID devices, researchers can study the reliability of trajectories and the invoked transportation risk issues, i.e., driving behavior detection [2,3], travel pattern recognition [4][5][6], and anomaly tracking in practice [4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the rapid evolution of artificial intelligence and machine learning technology also provides methodological support for datadriven PT passenger classification. Some previous studies identified the PT commuters based on the intelligent algorithm including association rules algorithm [10], convolutional neural networks (CNNs) [8], Naïve Bayes probabilistic model [11,12], support vector machine and decision tree [12], and statistical analysis model [13]. Zhang et al identified the commuters among numerous bus passengers by using the IC data with the cluster analysis [14].…”
Section: Introductionmentioning
confidence: 99%